O encerramento do programa de saúde escolar em Belo Borizonte: conseqüência desta ação na saúde bucal dos escolares - Regina Augusta de Castro Andrade (2008)
The aim of this study was to evaluate the oral health of scholars in BeloHorizonte after the end of the School Health Programme, comparing the data for 2007 to the same for 1995. The sample was calculated using the method of estimating proportions, which resulted in 722 scholars. Due to problems in the return of the TCLE, a larger number of students were chosen, and all of those who handed in the document were examined, finishing with a total number of 1.101 individuals. The data was gathered through an epidemiological investigation, analyzing the students caries index In 2007, 80% of the total number of scholars and 72% at the age of 12 were free of dental caries, while in 1995 (in Santos, 1996), 23.9% were in that situation. The CPOD found at the age of 12 was 0.61and the CPOS, 1.04. In comparison to the epidemiological investigation effected in 1995 (in Santos, 1996), there was a reduction of 4.5 times in the CPOD and of 7 times in the CPOS. As to the items in the CPOD, there was a decrease of 4 times in the number of dental caries, and of 6 times in the number of extractions and fillings. This reduction, however, is not evenly distributed among the population; it appears together with a polarization of the disease. Of the 18.411 teeth examined in 2007, less 1% showed problems that required treatment. A significant decreasewas observed in the CPOD and CPOS from 1995 to 2007, showing animprovement in the oral health of students in Belo Horizonte, and also indicating that the absence of a dentist in school did not have any influence on these results.